A squared + b squared = c squared
Define
![{x} = \left[\begin{array}{ccc}x_{1}\\x_{2}\end{array}\right]](https://tex.z-dn.net/?f=%7Bx%7D%20%3D%20%20%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7Dx_%7B1%7D%5C%5Cx_%7B2%7D%5Cend%7Barray%7D%5Cright%5D%20)
Then
x₁ = cos(t) x₁(0) + sin(t) x₂(0)
x₂ = -sin(t) x₁(0) + cos(t) x₂(0)
Differentiate to obtain
x₁' = -sin(t) x₁(0) + cos(t) x₂(0)
x₂' = -cos(t) x₁(0) - sin(t) x₂(0)
That is,
![\dot{x} = \left[\begin{array}{ccc}-sin(t)&cos(t)\\-cos(t)&-sin(t)\end{array}\right] x(0)](https://tex.z-dn.net/?f=%5Cdot%7Bx%7D%20%3D%20%20%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D-sin%28t%29%26cos%28t%29%5C%5C-cos%28t%29%26-sin%28t%29%5Cend%7Barray%7D%5Cright%5D%20x%280%29)
Note that
![\left[\begin{array}{ccc}0&1\\-1&09\end{array}\right] \left[\begin{array}{ccc}cos(t)&sin(t)\\-sin(t)&cos(t)\end{array}\right] = \left[\begin{array}{ccc}-sin(t)&cos(t)\\-cos(t)&-sin(t)\end{array}\right]](https://tex.z-dn.net/?f=%20%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D0%261%5C%5C-1%2609%5Cend%7Barray%7D%5Cright%5D%20%20%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7Dcos%28t%29%26sin%28t%29%5C%5C-sin%28t%29%26cos%28t%29%5Cend%7Barray%7D%5Cright%5D%20%3D%20%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D-sin%28t%29%26cos%28t%29%5C%5C-cos%28t%29%26-sin%28t%29%5Cend%7Barray%7D%5Cright%5D%20)
Therefore
Answer:
![60+10x=6](https://tex.z-dn.net/?f=60%2B10x%3D6)
Step-by-step explanation:
Hi there!
![4+\displaystyle \frac{2}{3} x=\frac{2}{5}](https://tex.z-dn.net/?f=4%2B%5Cdisplaystyle%20%5Cfrac%7B2%7D%7B3%7D%20x%3D%5Cfrac%7B2%7D%7B5%7D)
To get rid of the fraction
, multiply both sides of the equation by 3 (the denominator):
![3(4+\displaystyle \frac{2}{3} x)=3(\frac{2}{5})\\\\3*4+\frac{3*2}{3}x =\frac{3*2}{5} \\\\12+2x =\frac{6}{5}](https://tex.z-dn.net/?f=3%284%2B%5Cdisplaystyle%20%5Cfrac%7B2%7D%7B3%7D%20x%29%3D3%28%5Cfrac%7B2%7D%7B5%7D%29%5C%5C%5C%5C3%2A4%2B%5Cfrac%7B3%2A2%7D%7B3%7Dx%20%3D%5Cfrac%7B3%2A2%7D%7B5%7D%20%5C%5C%5C%5C12%2B2x%20%3D%5Cfrac%7B6%7D%7B5%7D)
To get rid of the fraction
, multiply both sides of the equation by 5 (the denominator):
![\displaystyle 5(12+2x) =5(\frac{6}{5})\\\\5*12+5*2x=\frac{5*6}{5} \\\\60+10x=6](https://tex.z-dn.net/?f=%5Cdisplaystyle%205%2812%2B2x%29%20%3D5%28%5Cfrac%7B6%7D%7B5%7D%29%5C%5C%5C%5C5%2A12%2B5%2A2x%3D%5Cfrac%7B5%2A6%7D%7B5%7D%20%5C%5C%5C%5C60%2B10x%3D6)
I hope this helps!
Answer:
8. adjacent 9. vertical 10. adjacent
Step-by-step explanation: